Adult education and regionalism - Juhász, Erika (Civilia, 2012)
In our study we will present a summary of one fragment of the researches concerning the relations of adult education and regionalism in Hungary. We will give an insight into the way the system of adult learning and the role of learning can be interpreted in Hungary. Following this we will highlight four researches which examined the relations of adult education and regionalism partly in terms of Hungary, partly from a broader, European point of view.
Keywords: Adult education; Regionalism; Hungary; Autonomous learning